Music Influences Hedonic and Taste Ratings in Beer - Reinoso Carvalho, Felipe; Velasco, Carlos; van Ee, Raymond; Leboeuf, Yves; Spence, Charles (Frontiers in Psychology, 2016)
The research presented here focuses on the influence of background music on the beer-tasting experience. An experiment is reported in which different groups of customers tasted a beer under three different conditions (N = 231). The control group was presented with an unlabeled beer, the second group with a labeled beer, and the third group with a labeled beer together with a customized sonic cue (a short clip from an existing song). In general, the beer-tasting experience was rated as more enjoyable with music than when the tasting was conducted in silence. In particular, those who were familiar with the band that had composed the song, liked the beer more after having tasted it while listening to the song, than those who knew the band, but only saw the label while tasting. These results provide support for the idea that customized sound-tasting experiences can complement the process of developing novel beverage (and presumably also food) events. Here we also suggest that involving musicians and researchers alongside brewers in the process of beer development, offers an interesting model for future development. Finally, we discuss the role of attention in sound-tasting experiences, and the importance that a positive hedonic reaction towards a song can have for the ensuing tasting experience.